Regulatory effect of vitamin D3 on proinflammatory processes in liver of diabetic mice - Labudzynskyi, D. O.; Kubaichuk, K. I.; Shymanskyi, I. O.; Veliky, M. M. (Reports of the National Academy of Sciences of Ukraine, 2016)
It is shown that the induction of pluripotent proinflammatory interleukin 6 (IL-6) in liver in diabetes is accompanied by increased expression of osteopontin (OPN) — molecular regulator of the synthesis of proinflammatory cytokines. Changes in the OPN and IL-6 expression correlate with a significant deficiency of vitamin D3 in organism. Normalization of the vitamin D3 level leads to a substantial reduction of the expression level of both OPN and IL-6 mRNA, showing the cytoprotective effect of cholecalciferol in diabetes-induced liver disorders.